2017
DOI: 10.4217/opr.2017.39.1.035
|View full text |Cite
|
Sign up to set email alerts
|

Distributions and Sources of Dissolved Organic Matter in Seawaters Surrounding Aqua Farms on the Haengwon-ri in Jeju-Island in Summer 2015

Abstract: : Concentrations of dissolved organic carbon (DOC), dissolved organic nitrogen (DON), dissolved organic phosphate (DOP), and colored dissolved organic matter (CDOM) were measured in the coastal sea off inland aqua farms in northeastern Jeju Island in summer 2015. The highest concentrations of DOC, DON, and DOP were revealed in the surface water off Hado-ri where the lowest salinity conditions prevailed (31.6). The concentrations of DOC, DON, and DOP in the surface water were lower in the inner stations (SH1-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…While we have extensively investigated the water column in the spring season, the satellite-derived data and previous references suggest that this region has a stronger thermohaline front in the winter season that continued into our observation period (Lie, 1985;Lie et al, 2000;Lie et al, 2015). Furthermore, the water temperature inversion (i.e., a higher temperature at a deeper depth) observed during our survey has also been reported in the spring and summer seasons, and the formation of the thermohaline front is generally explained as one of the main reasons for this occurrence (Kim, 2020;Kang and Moon, 2022;Kim et al, 2022;Yoo et al, 2023). In addition, the monthly distributions of SSTs and Chl-a and POC concentrations derived from the satellite data revealed intricate seasonal changes in hydrographic conditions and the corresponding dynamics of planktonic biomass in the northeastern East China Sea.…”
Section: Oceanographic Variability Of the Northeastern East China Sea...supporting
confidence: 84%
“…While we have extensively investigated the water column in the spring season, the satellite-derived data and previous references suggest that this region has a stronger thermohaline front in the winter season that continued into our observation period (Lie, 1985;Lie et al, 2000;Lie et al, 2015). Furthermore, the water temperature inversion (i.e., a higher temperature at a deeper depth) observed during our survey has also been reported in the spring and summer seasons, and the formation of the thermohaline front is generally explained as one of the main reasons for this occurrence (Kim, 2020;Kang and Moon, 2022;Kim et al, 2022;Yoo et al, 2023). In addition, the monthly distributions of SSTs and Chl-a and POC concentrations derived from the satellite data revealed intricate seasonal changes in hydrographic conditions and the corresponding dynamics of planktonic biomass in the northeastern East China Sea.…”
Section: Oceanographic Variability Of the Northeastern East China Sea...supporting
confidence: 84%
“…However, the average concentrations in the drainage (0.98 ± 0.20 mg/L) were relatively higher than in the coastal groundwater in Jeju Island. Although we could not directly obtain the water intake sample from the groundwater well owing to the lack of access authority, the DOC concentration in the fresh groundwater was consistently and significantly low in the coastal Jeju Island in different seasons (Cho et al 2021 ; Kim and Kim 2017a ; Kim and Kim 2017b ; Kim et al 2013 ; Song et al 2018 ). Additionally, the contribution of the fresh groundwater origin to the drainage and coastal water samples appeared to be significant based on the statistically lower salinity and pH values.…”
Section: Discussionmentioning
confidence: 99%
“…The red circles represent the sampling stations in area Gueom, as the control group, which are located in more than 5 km distance from the aquafarms. The red triangles represent the study sites for physicochemical parameters of the coastal groundwater in previous studies (Cho et al 2021;Kim and Kim 2017a;Kim and Kim 2017b;Kim et al 2013;Song et al 2018) characteristics in aquaculture. Nimptsch et al (2015) revealed that large amounts of anthropogenic dissolved organic carbon (DOC) with the most biodegradable protein-like FDOM derived from land-based aquaculture facilities are being discharged into the river system in the North Patagonian region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrient concentrations in the coastal area of Jeju are influenced by the submarine groundwater discharge (Hwang et al 2005). Moreover, the excrement of migrating birds may be partially responsible for the high concentration of organic matter in the local coastal waters in Jeju (Kim and Kim 2017).…”
Section: A C Bmentioning
confidence: 99%